This Novel Approach New Blend Assistive Accessory - SARAVANAN, C.BALA; MOHAN, G. (IJRDO -Journal of Computer Science Engineering, 2016)
The Hybrid Assistive Limb (also known as HAL) is a powered exoskeleton suit or cyber-type strap-onrobot suit developed by Japan's Tsukuba University and the robotics company CYBERDYNE. It has been intendedto sustain and expand the physical capabilities of its users, particularly people with physical disabilities. ProfessorYoshiyuki Sankai’s robot suit, dubbed HAL™ for “Hybrid Assistive Limb”, is a major feat in science andtechnology, which enables elderly people to perform everyday tasks with which they would otherwise struggle, suchas walking, climbing stairs or lifting heavy objects.